2011
DOI: 10.1111/j.1750-3841.2011.02507.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antioxidant Activity and Functional Properties of Chingshey Purple Sweet Potato Fermented Milk by Lactobacillus acidophilus, L. delbrueckii subsp. lactis, and L. gasseri Strains

Abstract: (1) In our study, we have employed the γ-aminobutyric acid (GABA), organic acid contents, total phenol content, anthocyanins content, DPPH, oxygen radical absorbance capacity, superoxide dismutase activity assay, and cytotoxicity assay to assess the functional properties of fermented CPSP milk by different lactic acid bacteria. (2) Our results have revealed that the fermented CPSP milk samples possess high GABA concentrations, organic acid contents, anthocyanins contents, and antioxidant activity. This will pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 36 publications
1
25
1
Order By: Relevance
“…Various compounds of plants with antioxidant properties have been shown to exert a number of therapeutic effects in animal models of hypertension, which supports the hypothesis that reactive oxygen species (ROS) are involved in the progression of hypertension (29). In a previous study, we demonstrated that the fermentation procedure could further elevate anthocyanin levels and antioxidative activity significantly in PSPY with multi-strain probiotics (20). Additionally, the supplementation of probiotics may influence host intestinal microflora and subsequently improve cardiovascular functions.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Various compounds of plants with antioxidant properties have been shown to exert a number of therapeutic effects in animal models of hypertension, which supports the hypothesis that reactive oxygen species (ROS) are involved in the progression of hypertension (29). In a previous study, we demonstrated that the fermentation procedure could further elevate anthocyanin levels and antioxidative activity significantly in PSPY with multi-strain probiotics (20). Additionally, the supplementation of probiotics may influence host intestinal microflora and subsequently improve cardiovascular functions.…”
Section: Discussionmentioning
confidence: 73%
“…In a previous study, we demonstrated that purple sweet potato (PSP) [Ipomoea batatas (L.) Lam.] contains high levels of anthocyanin and can easily grow in subtropical areas through fermentation by 3 lactic acid bacteria (LAB), with high levels of GABA (20). However, the protective effects of probiotic-fermented milk and its derivatives, such as GABA on cardiac apoptosis have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Hidalgo et al (2012) reported that bacterial fermentation of a mixture of anthocyanins resulted in the formation of gallic, syringic and p-coumaric acids. Fermentation changes the forms of anthocyanins, degrading them to smaller byproducts that are more easily absorbed and with altered bioactivity (Vergara-Salinas et al 2013;Wu et al 2012) although some anthocyanin glycosides were also detected in serum and urine. Anthocyanin aglycones are reported to have greater bioavailability glycosylated anthocyanins.…”
Section: Discussionmentioning
confidence: 99%
“…Fermentation of milk with Chingshey purple sweet potato by lactic acid bacteria strains such as Lactobacillus acidophilus increases antioxidant activities as measured by 1,1-diphenyl-2-picryl-hydrazyl (DPPH) radicals and enhances its scavenging effects against superoxide anion radicals (Wu et al 2012). Fermentation of black bean extracts with Aspergillus increases DPPH free radical-scavenging activity, Fe 2?…”
Section: Discussionmentioning
confidence: 99%
“…PSPAs exhibit diverse biological activities, including antioxidant (Wu, Tsai, Hwang, & Chiu, 2012;Zhang et al, 2013), anticancer (Lim et al, 2013;Ye, Meng, Yan, & Wang, 2010), _ENREF_7antidiabetic (Jang, Kim, Kim, Kim, & Lee, 2013;Zhao, Yan, Lu, & Zhang, 2013), anti-inflammatory Zhang et al, 2009), and hepatoprotective activities (Sun, Mu, Liu, Zhang, & Chen, 2014;Wang, Tong, et al, 2014;. Moreover, PSPAs containing aromatic acylated glycosyl groups have been shown to have high pH and thermo-stability (Giusti & Wrolstad, 2003;Kim et al, 2012).…”
Section: Introductionmentioning
confidence: 97%